THE EFFECT OF FIELD TRIP METHOD ON STUDENTS’ WRITING DESCRIPTIVE TEXT ABILITY (A study at the Eighth Grade of SMP Swasta Advent Barus in 2020/2021 Academic Year) - suriani simamora surianisimamora (JURNAL LINER (Language Intelligence and Educational Research), 2022)
The aims of this research are to know: 1) the application of field trip method in teaching writing descriptive text 2) the students’ writing descriptive text ability before and after using field trip method 3) Whether there is a significant effect of field trip method on students’ writing descriptive text ability at the eighth grade of SMP Swasta Advent Barus. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research is all of the eighth grade students’ of SMP Swasta Advent Barus which consist of 70 students. Sample are VIII A which consist of 22 students which taken by purposive sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The results of this research are: 1) the application of field trip method is 3.8, it is categorized “very good” 2) the mean score of students writing descriptive text ability is 47 it is categorized “fail”. Meanwhile, after using field trip method is 72, it is categorized “good”. 3) There is a significant effect of using field trip method on students’ writing descriptive text ability at the eighth grade of SMP Swasta Advent Barus. The result of data analysis shows that ttest is higher than ttable (ttest16. 90 > ttable2.05). So, the hypothesis is accepted. It means that, there is a significant effect of field trip method on students’ writing descriptive text ability at the eighth grade of SMP Swasta Advent Barus in 2020/2021 Academic Year.